The Restless Compendium Interdisciplinary Investigations of Rest and Its Opposites - Callard, Felicity; Staines, Kimberley; Wilkes, James (Springer Nature, 2016)
This interdisciplinary book contains 22 essays and interventions on rest and restlessness, silence and noise, relaxation and work. It draws together approaches from artists, literary scholars, psychologists, activists, historians, geographers and sociologists who challenge assumptions about how rest operates across mind, bodies, and practices. Rest's presence or absence affects everyone. Nevertheless, defining rest is problematic: both its meaning and what it feels like are affected by many socio-political, economic and cultural factors. The authors open up unexplored corners and experimental pathways into this complex topic, with contributions ranging from investigations of daydreaming and mindwandering, through histories of therapeutic relaxation and laziness, and creative-critical pieces on lullabies and the Sabbath, to experimental methods to measure aircraft noise and track somatic vigilance in urban space. The essays are grouped by scale of enquiry, into mind, body and practice, allowing readers to draw new connections across apparently distinct phenomena. The book will be of interest to students and scholars across a range of disciplines in the social sciences, life sciences, arts and humanities.